Assessment of Farmer Vulnerability and Adaptation to Climate Change in Sunderbans Ecosystem (Indian Journal of Extension Education, 2010)
Climate change has emerged as one of the most urgent issues of investigation and deliberation among people of walks of life be it statesmen, planners and policy makers; climate, environmental and biological scientists; or actors, activists and academicians. The study was conducted in 24-South pargana district of West Bnegal to assess the level of vulnerability of farming community and their capability and strategy for adaptation to climate change. With the calculated vulnerability index, a majority of the respondents (about 47 per cent) were found in highly vulnerable. Group followed by about 37 per cent in vulnerable group; while about 17 per cent in moderately vulnerable group. Innovativeness, mass media source of information, education and knowledge of technology, occupation of agriculture, social participation, scientific orientation and risk orientation were identified as predictor variables for vulnerability index. Extreme poverty, by lack of education and proper knowledge about adaptive practices, lack of information facilities with forecasting and early warning system, lack of awareness about climate change issues, lack of aptitude towards resource conservation and adaptation needs were reported as the major constraints by the farmers in their adaptation endeavours.